2006
DOI: 10.1098/rspa.2006.1773
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the role of ions in particle nucleation under atmospheric conditions

Abstract: Experimental studies of aerosol nucleation in air, containing trace amounts of ozone, sulphur dioxide and water vapour at concentrations relevant for the Earth's atmosphere, are reported. The production of new aerosol particles is found to be proportional to the negative ion density and yields nucleation rates of the order of 0.1–1 cm −3  s −1 . This suggests that the ions are active in generating an atmospheric reservoir of small thermodynamically stable cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 34 publications
(38 reference statements)
4
121
0
1
Order By: Relevance
“…Shaviv (2002) proposed a CR-climate connection on the timescale of 10 8 years due to the transit of the solar system through the Galactic spiral arms during its orbit around the Galactic center. The argument Article published by EDP Sciences A120, page 1 of 7 assumes that the low-altitude cloud coverage increases due to an increased formation of cloud-condensation nuclei when the CR flux is high (Svensmark et al 2007). Thus, an anticorrelation between temperature and CR flux is to be expected and is indeed reported by Shaviv & Veizer (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Shaviv (2002) proposed a CR-climate connection on the timescale of 10 8 years due to the transit of the solar system through the Galactic spiral arms during its orbit around the Galactic center. The argument Article published by EDP Sciences A120, page 1 of 7 assumes that the low-altitude cloud coverage increases due to an increased formation of cloud-condensation nuclei when the CR flux is high (Svensmark et al 2007). Thus, an anticorrelation between temperature and CR flux is to be expected and is indeed reported by Shaviv & Veizer (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Such reactions were first suggested in Svensmark et al [10], and also in a recent experiment [26] looking at isotope fractionation of sulphur from either UV or from ion-induced generation of H 2 SO 4 , where the sulphur isotope fractionation was used to distinguish the different pathways leading to H 2 SO 4 . It was found in the presence of ionization alone, that for each ion-pair 27.8·10 6 H 2 SO 4 molecules were produced, using extreme gas mixing ratios, i.e.…”
mentioning
confidence: 99%
“…Experimental evidence for a microphysical mechanism was first reported in 2007 [10] and further experiments have recently added to its credibility [11,12]. These experiments initially showed that an increase in ionization leads to an increase in the formation of ultrafine aerosols (≈ 3 nm), but in the real atmosphere such small particles have to grow by coagulation and intake of condensable gases to become cloud condensation nuclei (CCN) (> 50 nm) in order to have an effect on clouds [13, chapter 17].…”
mentioning
confidence: 99%
“…Thus, despite the IIN mechanism is believed to work mainly under clear sky conditions, it can also communicate solar activity to cloudiness. Experimental evidence for IIN have been obtained by Eichkorn et al (2002); Lee et al (2003) and Svensmark et al (2007). It was shown that changes in the global atmospheric circuit can influence cloud microphysics (Tinsley, 2000).…”
Section: Cosmic Ray Flux and Terrestrial Climatementioning
confidence: 95%